Answer:
x= -3 x = 1/2 x=-2
Step-by-step explanation:
f(x)=(x+3) (2x-1)(x+2)
Set equal to zero
0 =(x+3) (2x-1)(x+2)
Using the zero product property
x+3 =0 2x-1 =0 x+2 =0
x= -3 2x =1 x = -2
x= -3 x = 1/2 x=-2
Answer: point form
1. (6,24)
2.(-4,-12)
3.(3,15)
4. (-5,-20)
5. (2,4)
6.(-1,-4)
7.(-3,-9)
8.(-4,-8)
9.(3,9)
10.(-6,-30)
Step-by-step explanation:
Answer:
The Correct Answer are B and D
Step-by-step explanation:
Answer:
30
Step-by-step explanation:
62 = 2x+2
62-2 = 60
60/2 = 30
450=50x this should be correct :)